KEARIFAN LOKAL BERTANI PADI SAWAH DI KELURAHAN TARATARA KECAMATAN TOMOHON BARAT KOTA TOMOHON (LOCAL WISDOM OF RICE FARMING IN TARATARA KELURAHAN TOMOHON BARAT KOTA TOMOHON) - Sonya Ruth Nongko; Jane Sulinda Tambas; Elsje Pauline Manginsela (Sam Ratulangi University, 2021)
This study aims to identify and describe the local wisdom of lowland rice farming in Taratara Village. This research has been going on for 3 (three) months starting from February to April 2020, in Taratara Village, West Tomohon District, Tomohon City. This research was conducted in a survey using primary data obtained through in-depth interviews using a list of questions as a prepared guide, also through documentation and secondary data obtained from the village office. The data analysis used in this research is descriptive qualitative analysis which is described / expressed in words. Then the data obtained is presented in tabular form. The results showed that the local wisdom of lowland rice farming in the Taratara Village community at the time of land preparation, namely, a) worked before sunrise; b) using traditional tools (hoe, pajeko and rake); c) not clearing the edges of land (litir) and local wisdom that is still being applied today is wisdom c) not clearing litir (land edges), while a) and b) are extinct or not being used anymore. Local wisdom in nurseries, namely, a) selecting superior seeds; b) choosing the middle month (a good time) and what is still being done is b) choosing superior seeds. Local wisdom on land cultivation, namely, a) using traditional tools, namely pacol (hoe), pajeko, and garu; b) leveling the land, making the soil perfectly muddy and local wisdom at this stage is still being carried out today. Local wisdom at the planting stage, namely, a) mapalus farming; b) determine a good day (middle month); c) pray to the ancestors in the local language of Tombulu; d) not shouting when planting, and to all local wisdom this is no longer done at the planting stage. Local wisdom at the maintenance stage, namely, a) using traditional tools such as pacol (hoe), peda (sickle) and garu; c) using natural fertilizers (rotting grass and manure); d) using a scarecrow and a neigh (a tin filled with stones); d) methods and habits of irrigating lowland rice and local wisdom that are no longer practiced is b) using natural fertilizers. Local wisdom at the harvest stage, namely, a) singing the song of thanksgiving (ma'zani); b) mapalus farmer; c) determine a good day (middle month); d) customary practices at harvest; and what is still being done is d) customary ways of harvesting. Local wisdom is still maintained because there are still peasant communities who respect culture and customs, while local wisdom is not practiced such as mapalus peasants and ma'zani chants, this local wisdom strengthens the bonds of brotherhood and a high sense of cohesiveness because local wisdom is carried out together and in groups, but because of the modern technology that entered the farmers absorb and get a more efficient time in the process of cultivating lowland rice. The advantages of farmers in maintaining local wisdom until now is to strengthen the ties of brotherhood among the community and continue to preserve culture so that it is not lost due to the entry of modern culture.